Clinical Molecular Immunohistochemistry Mismatch Repair Mutations in Lynch Syndrome in Patients Under 50 Years: A Systematic Review - Bogdan Adrian Manta; Adrian Cosmin Ilie; Felicia Marc; Daciana Nistor; Patricia Octavia Mazilu; Claudia Borza (Biomedicines)
Background and Objectives: Lynch syndrome (LS), an autosomal dominant condition arising from germline mutations in mismatch repair (MMR) genes, is a major cause of hereditary early-onset colorectal cancer (CRC). Although patients diagnosed before age 50 represent a critical subgroup where Lynch syndrome might be more prevalent, data on the precise frequency, clinical outcomes, and molecular correlates remain heterogeneous across studies. This systematic review was conducted to (1) estimate the prevalence of MMR deficiency (dMMR) and confirmed LS in patients diagnosed with CRC before the age of 50, and (2) examine immunohistochemistry (IHC) mismatch repair testing patterns and associated molecular findings (BRAF mutations, MLH1 promoter hypermethylation, somatic MMR gene alterations). Methods: Following a predefined search strategy in PubMed, Scopus, and Web of Science, five relevant studies were identified (n = 5). Each study comprised patients younger than 50 who underwent IHC-based tumor screening. Data extraction covered demographic details, number of patients tested, proportion with abnormal IHC, frequency of somatic or germline MMR gene mutations, and method of classification into sporadic dMMR vs. LS. Quality assessment was performed using recommended scales for observational studies. Results: Among 5 studies totaling 960 early-onset CRC patients, the frequency of dMMR CRC ranged from 8.4% to 19.1%. The confirmed prevalence of LS among all young-onset CRC was between 5.0% and 5.9% in three studies but reached 8.9% in another and 5.1% in yet another. Across all studies, the presence of right-sided tumors and histopathological features such as tumor-infiltrating lymphocytes were more common in dMMR cancers. Incorporation of MLH1-promoter hypermethylation and/or BRAF V600E mutation testing aided discrimination of sporadic dMMR CRC from germline LS cases. Conclusions: The prevalence of LS in CRC patients younger than 50 is clinically significant, at approximately 5–9%. Routine IHC-based MMR screening is both feasible and effective for detecting LS in early-onset CRC. Further research is needed to standardize universal testing protocols, delineate the role of additional molecular assays, and ensure comprehensive genetic counseling for at-risk individuals.